2010
DOI: 10.1134/s002136401006010x
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting triplet spin valve

Abstract: We study the critical temperature T_c of SFF trilayers (S is a singlet superconductor, F is a ferromagnetic metal), where the long-range triplet superconducting component is generated at noncollinear magnetizations of the F layers. We demonstrate that T_c can be a nonmonotonic function of the angle \alpha between the magnetizations of the two F layers. The minimum is achieved at an intermediate \alpha, lying between the parallel (P, \alpha=0) and antiparallel (AP, \alpha=\pi) cases. This implies a possibility … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
126
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(139 citation statements)
references
References 16 publications
5
126
1
7
Order By: Relevance
“…As spin-one triplet pairs are immune to pair breaking by the exchange field in F, the proximity effect coupling between S and F layers is enhanced. As with the conventional superconductor-normal metal proximity effect, the increased 'leakage' of pairs from the S layer should reduce the singlet pair amplitude within it and hence decrease the T C of the structure 12 . A number of experiments have been performed to test these predictions: for example, in S-F 0 -F structures, both Leksin et al 13 and Zdravkov et al 14 recently demonstrated a minimum in T C when the F and F 0 layers were orthogonal-the configuration that theoretically maximizes singlet-triplet pair conversion.…”
mentioning
confidence: 99%
“…As spin-one triplet pairs are immune to pair breaking by the exchange field in F, the proximity effect coupling between S and F layers is enhanced. As with the conventional superconductor-normal metal proximity effect, the increased 'leakage' of pairs from the S layer should reduce the singlet pair amplitude within it and hence decrease the T C of the structure 12 . A number of experiments have been performed to test these predictions: for example, in S-F 0 -F structures, both Leksin et al 13 and Zdravkov et al 14 recently demonstrated a minimum in T C when the F and F 0 layers were orthogonal-the configuration that theoretically maximizes singlet-triplet pair conversion.…”
mentioning
confidence: 99%
“…Recent theoretical studies (see, for example,reviews [2][3][4][5][6][7][8]) have predicted the generation of a long-range triplet component of a superconducting condensate in S/F-structures. As follows from the theory proposed by Fominov et al [9], the presence of a minimum of the superconducting transition temperature T c in e-mail: kamandi@mail.ru the vicinity of the orthogonal configuration of the magnetizations clearly indicates the generation of the longrange triplet component. We have experimentally confirmed the existence of the long-range triplet component for the CoO x /Fe1/Cu/Fe2/Pb superconducting spin-valve structure [10].…”
Section: Introductionmentioning
confidence: 88%
“…The significant discrepancy between theory and experiment can be caused by two factors. In the theory proposed by Fominov et al [9], the F-layers were represented by weak ferromagnets, whereas permalloy is not ferromagnetic. In addition, we ignored the limitation of the transparency of the Py1/Cu/Py2 interface, as was done in the theoretical studies of Deminov et al [21,22], because, in our case, this parameter would be free.…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of implementations of Josephson control elements were proposed recently, among which the structures containing F layers in the weak link region are of greatest interest [1][2][3] . Various types of superconducting spin-valve structures including two or more ferromagnetic layers have been proposed [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . The mutual orientations, parallel or antiparallel, of magnetizations of the layers determine critical currents and critical temperatures of the structures.…”
mentioning
confidence: 99%